DiceCT Analysis of the Extreme Gouging Adaptations Within the Masticatory Apparatus of the Aye‐Aye (Daubentonia madagascariensis). Issue 2 (12th November 2019) - Dickinson, Edwin; Kolli, Shruti; Schwenk, Alysa; Davis, Cassidy E.; Hartstone‐Rose, Adam
ABSTRACT: Relative to all other primates, the aye‐aye ( Daubentonia madagascariensis ) exists at the extremes of both morphology and behavior. Its specialized anatomy—which includes hypselodont incisors and highly derived manual digits—reflects a dietary niche, unique among primates, which combines tap‐foraging with gouging to locate and extract wood‐boring larvae. Here, we explore the impact of this extreme dietary ecology upon the masticatory musculature of this taxon with reference to a second, similarly sized but highly generalist lemuriform—the mongoose lemur ( Eulemur mongoz ). Using non‐destructive, high‐resolution diffusible iodine‐based contrast‐enhanced computed tomography techniques, we reconstruct the three‐dimensional volumes of eight masticatory muscles, and, for the first time in strepsirrhines, isolate and visualize their constituent muscle fascicles in situ and in three dimensions. Using these data, we report muscle volumes, forces, and fascicle lengths from each muscle portion, as well as their orientation relative to two standardized anatomical planes. Our findings demonstrate the overbuilt nature of the aye‐aye's masticatory apparatus, in which each muscle possesses an absolutely and relatively larger muscle volume and PCSA than its counterpart in the mongoose lemur. Likewise, for several adductor muscles, aye‐ayes also possess relatively greater fascicle lengths. Finally, we note several unusual features within the lateral pterygoid of the aye‐aye—the muscle most responsible for jaw protrusion—that relate to force maximization and reorientation. As this jaw motion is critical to gouging, we interpret these differences to reflect highly specific specializations that facilitate the aye‐aye's extreme subsistence strategy. Anat Rec, 2019. © 2019 American Association for Anatomy Anat Rec, 303:282–294, 2020. © 2019 American Association for Anatomy